SISTEM UJIAN INTRANET DENGAN TEKNIK RANDOM MENGGUNAKAN CODEIGNITER (Information Technology and Telematics, 2014)
Abstrack -- Exam is one way to evaluate the learning process, but cheating is still a factor common problem in education. Randomization in the presentation about a solution that is often used in dealing with fraud. But there needs to be an additional method that a smaller chance of fraud is to bring several different about each student and the difficulty level classification. In this case the authors try to apply such techniques to create an array of random matrix where the index stratified and randomize elements of each level. The results of this study resulted in the software (software) system in the form of intranet web-based test information using PHP and MYSQL in SMK 7 Semarang. Experiments performed focused on how to display different matter - the difference between the student but has the same weight. From the test results show the system has been running according to plan. The use RandomMatrix been able to generate random problems with similar levels of difficulty for each student. For the future development of the level of difficulty can be created flexibly composed not only easy, medium and difficult course. Keywords -- Exam, Random question, cheating students, exam scores.